Strategi Mencegah Dan Mengatasi Diare Di Kelurahan Jayaloka Kabupaten Empat Lawang - Rolanda, Koko; Etika, Etika; Asmili, Yuti; Winda, Sukma; Cahyani, Mentari; Habibi, Julius; Rohani, Tuti; Sari, Fikitri Marya (Jurnal Gotong Royong, 2025)
The role of the Community in prevention and hand washing efforts intended for the community in the hope of reducing the incidence of diarrhea. Formal awareness activities to create a healthy and prosperous RT. 003/RW. 01 community with proper diarrhea and handwashing counseling. The method used in Community Service is by way of counseling, the correct handwashing demonstration. The results of this adoption will highlight the journal and may reduce the prevalence of the incidence of diarrhea in RW.01 Kelurahan Jaya Loka 1. This community service will be done with several symptoms, namely observation on diarrhea and prevention disease, and measurement of knowledge done after pretest and posttest. The result of this community service activity is the result of a general pretest which shows that the beginning of PKK seen diarrhea disease is still lacking. The posttest result in general shows that the participants of PKK mothers look diarrhea has been a better improvement. Health Research and Entrepreneurship Research Report to Increase Knowledge of Mother of PPK RT. 003/RW. 01 Kelurahan Jaya Loka 1 Kabupaten Empat Lawang.